Pengujian Prototipe Sistem Jasa Pengembangan Aplikasi Menggunakan Metode System Usability Scale - Kusuma, I Kadek Agus Wijaya; Giri, Gst. Ayu Vida Mastrika (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024, 2024)
The utilization of websites to spread information related to services is commonly used by service providers, including those in application development services. In developing a website, designing an interactive interface becomes an important aspect. This has an impact on the effectiveness and efficiency of the website, as well as the user experience. Therefore, the participation of users in designing the website, considering their needs and issues they face is essential. To ensure the website meets user’s standards and expectations, usability testing is conducted on the website prototype. This research uses the System Usability Scale (SUS) method. The SUS scores from the testing serve as a benchmark to evaluate the effectiveness, efficiency, and optimization of the user experience of the website prototype. To achieve high SUS scores, the website prototype must be capable of providing effective and efficient solutions to user’s issues while also supplying their needs. A website prototype with high scores can be considered to have met user’s standards and expectations, therefore it is ready for implementation.